COMPUTATIONAL DRUG DESIGN AND MOLECULAR DYNAMICS OF PHENYL BENZAMIDE DERIVATIVES AS PARP-1 INHIBITORS FOR BREAST CANCER THERAPY - RAJ, PULLA PRUDVI; PALATI, DIVYA JYOTHI; T. K., PRAVEEN; B., GOWRAMMA (International Journal of Applied Pharmaceutics, 2025)
Objective: Poly (ADP-ribose) polymerase-1 (PARP1) plays a vital role in Deoxyribonucleic Acid (DNA) repair and cell survival. Given its importance in cancer progression, PARP1 inhibitors are promising therapeutic agents. This study aims to design and evaluate 3-((3,4-dihydroisoquinolin-2(1H)-yl) sulfonyl)-N-phenyl benzamide derivatives as potential PARP1 inhibitors using computational approaches. Methods: Molecular docking was performed to assess the binding affinity of the designed compounds with PARP1. Molecular Mechanics-Generalized Born Surface Area (MM-GBSA) calculations were used to validate binding free energy and stability. Molecular dynamics (MD) simulations analyzed complex stability over time. Results: Docking analysis showed that compound 2D had a Glide score of-6.53 kcal/mol, comparable to Olaparib (-6.46 kcal/mol). Key interactions with Tyr896, Arg878, Asp766, and Ser904 contributed to its stability. MD simulations confirmed minimal Root mean Square Deviation (RMSD) (1.2 to 2.7 Å) and Root mean Square Fluctuation (RMSF) (0.5 to 0.9 Å) fluctuations, indicating strong binding stability. Binding free energy analysis showed that compound 2D (-87.20 kcal/mol) exhibited a binding affinity close to the standard drug (Olaparib) (-88.81 kcal/mol). Conclusion: Compound 2D demonstrated strong and stable interactions with PARP1, comparable or superior to Olaparib. These findings suggest that compound 2D is a promising lead candidate for PARP1-targeted therapy, warranting further preclinical and biological validation.